A study on the customers’ satisfaction towards homestay program in Kelantan / Wan Patimah Wan Hamzah - Wan Hamzah, Wan Patimah (2008)
This research was conducted to study the customer satisfaction toward Homestay Program in Kelantan. The objective of this research is to determine the factors that influence customer satisfaction towards Homestay Program in Kelantan. This study also was conducted to identify what are the most and least influencing factors for customer satisfaction towards Homestay Program in Kelantan. Finally, the purpose of this study is to recommend some idea and suggestion to improve the level of customer satisfaction toward Homestay Program in Kelantan. The researcher had distributed the questionnaire among 100 customers of Homestay Program in Kelantan. Service quality, environment, ambience of building, owner courtesy and price value are the independent variables that being selected by the researcher. After collecting the data and analyze it, the result shows that there is relationship between service quality, environment, ambience of building and owner courtesy with the customer satisfaction towards Homestay Program in Kelantan. The result also shows that there is no relationship between price value and customer satisfaction toward Homestay Program in Kelantan. By conducting this research also, the researcher hopes that Ministry of Tourism, Kelantan State Action Council and the owner of the Homestay Program can improve the level of customer satisfaction toward Homestay Program in Kelantan.